2012
DOI: 10.1039/c1cc16148b
|View full text |Cite
|
Sign up to set email alerts
|

1,3,5-Triphenylbenzene fluorophore as a selective Cu2+sensor in aqueous media

Abstract: Three water-soluble fluorophores are synthesized from 1,3,5-tris-(4'-iodophenyl)benzene. The compound with salicylate groups exhibits a selective fluorescent quenching by Cu(2+)via a static quenching mechanism. The addition of Triton X-100 improves the quantum efficiency of the fluorophore as well as the detection limit for Cu(2+) from 6.49 to 0.19 ppb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…There have been a few reports on the addition of surfactants, which can enhance the sensitivities for this class of fluorescent sensors [15,17]. The work by Chattopadhyay [22] demonstrated the addition of the anionic SDS as a simple way to maximize the efficiency of an indoloquinolizine fluorosensor for Cu(II).…”
Section: Discrimination Of Cu(ii) From Fe(ii) By Addition Of Surfactantmentioning
confidence: 98%
See 1 more Smart Citation
“…There have been a few reports on the addition of surfactants, which can enhance the sensitivities for this class of fluorescent sensors [15,17]. The work by Chattopadhyay [22] demonstrated the addition of the anionic SDS as a simple way to maximize the efficiency of an indoloquinolizine fluorosensor for Cu(II).…”
Section: Discrimination Of Cu(ii) From Fe(ii) By Addition Of Surfactantmentioning
confidence: 98%
“…Recent examples of research works on fluorescent detection of Cu(II) in the literatures demonstrated the use of phenanthrene-base calix [4]arene [10], coumarin [11], dansyl-antipyrine dyad [12], and benzoimidazole [13] as the sensors. In our research program, we aim to design and construct a library of fluorophores which exhibited selective fluorogenic responses towards metal (II) ions, proteins, and nitroaromatic compounds in solution phase [15][16][17][18][19]. In this paper we reported the synthesis and study of fluorescent compounds 1-2 (Scheme 1) which contain fluorene as the fluorescent signal transducer and the salicylic acid groups as the receptor for metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridoxal hydrochloride (0.406 g, 2 mM) was dissolved in absolute methanol (15 mL The Schiff base ligand HL was synthesized by condensing pyridoxal hydrochloride with N,N-dimethylethylenediamine under reflux in MeOH and characterized by 1 H NMR, 13 C NMR and FTIR spectroscopy (Fig. 1).…”
Section: Synthesis Of Hlmentioning
confidence: 99%
“…However, all of these methods require expensive and sophisticated instruments combined with complicated sample pretreatment and therefore impractical for a real-time experiment. Recently, metalselective fluorescent chemosensors have attracted intense attention for their simple, economical and real-time tracking of metal ions in environmental samples [11,12] Cu 2+ is a typical ion that leads to decreased fluorescent emissions owing to quenching of the fluorescence by mechanisms inherent to the paramagnetic species [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the critical role of copper ion in the biological systems and environment, development of rapid and sensitive probes for the detection of Cu 2+ in biological and environment systems becomes very important. Due to the paramagnetic nature of Cu 2+ , the binding of Cu 2+ could induce intrinsic fluorescence quenching and lead to a turn-off signal [5,6]. Interestingly, the resultant non-fluorescence ensemble Cu 2+ complex could be explored as an anion selective probe.…”
mentioning
confidence: 97%